Mining Engineering Annual Review 1975 - Industrial Mineral Commodities (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1976)
Inflation, fuel shortages, environmental restrictions, and a worldwide recession that sharply curtailed the demand for goods and services, were the main causes for the poor performance & virtually all industrial minerals in 1975. This poor showing was not a surprise. As Felix Shay correctly predicted in his introductory remarks to last year's industrial Minerals Review (ME, Feb. 1975, p. 70), ". . . the minerals industry will soon be facing falling demand as a consequence of sharp declines in auto production, housing, appliances, and other consumer goods. Moreover, when sales weaken. the high-volume, low-priced industrial minerals will incur sharply.